National Strategy for Maritime Security: The British Model (2014-2017) - Ryantono, Khansa Aqila (Andalas Journal of International Studies (AJIS), 2022)
This article aims to analyse the United Kingdom National Strategy on maritime security to deter risks and threats in its maritime domain and to secure its national interest beyond border. Using the theory of Sea power, the author analysed the growing complexity and challenges in global maritime domain as well as the UK’s outward looking strategy that aims to influence and project its power through Maritime Security Governance. By using qualitative research method, the findings of this study are that the UK emphasizes on developing defence engagement, economic development and diplomatic influence to secure its maritime interest by addressing the importance of maritime security government to fully implement the National Maritime Security Strategy and define actions to be taken in facilitating the objectives.